The Clover Girls [large type] - Shipman, Viola (Center Point Large Print, 2021)
"Elizabeth, Veronica, Rachel and Emily met at Camp Birchwood as girls in 1985, where over four summers they were the Clover Girls--inseparable for those magical few weeks of freedom--until the last summer that pulled them apart. Now approaching middle age, the women are facing challenges they never imagined as teens, struggles with their marriages, their children, their careers, and wondering who it is they see when they look in the mirror. Then Liz, V and Rachel each receive a letter from Emily with devastating news. She implores the girls who were once her best friends to reunite at Camp Birchwood one last time, to spend a week together revisiting the dreams they'd put aside and repair the relationships they'd allowed to sour. But the women are not the same idealistic, confident girls who once ruled Camp Birchwood, and perhaps some friendships aren't meant to last forever ..."--